2018
DOI: 10.1155/2018/5101937
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Properties of R-High Density Polyethylene Composites Reinforced with Wheat Straw Particleboard Dust and Basalt Fiber

Abstract: The effect of individual and combined particleboard dust (PB dust) and basalt fibers (BFs) on mechanical and thermal expansion performance of the filled virgin and recycled high density polyethylene (HDPE) composites was studied. It was shown that the use of PB dust had a positive effect on improving mechanical properties and on reducing linear coefficient of thermal expansion (LCTE) values of filled composites, because the adhesive of the particle board held the wheat straw fibers into bundles, which made PB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Previous work was studied by Idress(27), who found that the highest tensile strength for HDPE composite with a mold surface temperature of 50 °C. By comparing with this work, Yu et al(28) reported in their findings regarding the mechanical characterizations for particleboard dust (PB dust) and basalt fibers (BFs)/Recycled (R-HDPE), they found that the tensile strength was increased with the loading of (1BP dust:1BFs) in HDPE composite. They reported that the tensile strength of 1PB:1BFs/RHDPE composite was 28.3 MPa while the virgin RHDPE matrix was 19.4 MPa.…”
supporting
confidence: 56%
“…Previous work was studied by Idress(27), who found that the highest tensile strength for HDPE composite with a mold surface temperature of 50 °C. By comparing with this work, Yu et al(28) reported in their findings regarding the mechanical characterizations for particleboard dust (PB dust) and basalt fibers (BFs)/Recycled (R-HDPE), they found that the tensile strength was increased with the loading of (1BP dust:1BFs) in HDPE composite. They reported that the tensile strength of 1PB:1BFs/RHDPE composite was 28.3 MPa while the virgin RHDPE matrix was 19.4 MPa.…”
supporting
confidence: 56%
“…Recycling waste plastics and agricultural residues is an excellent option for global sustainable development, and it is now a prevalent practice in the manufacturing sector [ 94 , 95 ]. Studies have demonstrated that various industrial and domestic wastes can be recycled and utilized as concrete elements in the development of green concrete [ 9 ].…”
Section: Sustainability Of Diatomaceous Earth As a Concrete Productio...mentioning
confidence: 99%
“…Bio-composites synthesized from natural fibers and recycled plastics are in considerable demand across the world. Natural fibers are directly obtained as a waste product after harvesting a variety of crops such as rice husk, 1 wheat straw, 2 rice straw, 3 sugarcane bagasse, 4 cotton stalk, 5 and corn husk. 6 The pre-dominant issue is the burning and discarding of waste crop residues in the open land as it causes many environmental hazards.…”
Section: Introductionmentioning
confidence: 99%